A Radiographic Assessment of Failed Anterior Cruciate Ligament Reconstruction: Can Magnetic Resonance Imaging Predict Graft Integrity?. (July 2014) - Waltz, Robert A.; Solomon, Daniel J.; Provencher, Matthew T.
Background: Magnetic resonance imaging (MRI) showing an "intact" anterior cruciate ligament (ACL) graft may not correlate well with examination findings. Reasons for an ACL graft dysfunction may be from malpositioned tunnels, deficiency of secondary stabilizers, repeat injuries, or a combination of factors. Purpose: To evaluate the concordance/discordance of an ACL graft assessment between an arthroscopic evaluation, physical examination, and MRI and secondarily to evaluate the contributing variables to discordance. Study Design: Case series; Level of evidence, 4. Methods: A total of 50 ACL revisions in 48 patients were retrospectively reviewed. The ACL graft status was recorded separately based on Lachman and pivot-shift test data, arthroscopic findings from operative reports, and MRI evaluation and was categorized into 3 groups: intact, partial tear, or complete tear. Two independent evaluators reviewed all of the preoperative radiographs and MRI scans, and interrater and intrarater reliability were evaluated. Concordance and discordance between a physical examination, arthroscopic evaluation, and MRI evaluation of the ACL graft were calculated. Graft position and type, mechanical axis, collateral ligament injuries, chondral and meniscal injuries, and mechanism of injury were evaluated as possible contributing factors using univariate and multivariate analyses. Sensitivity and specificity of MRI to detect a torn ACL graft and meniscal and chondral injuries on arthroscopic evaluation were calculated. Results: The interobserver and intraobserver reliability for the MRI evaluation of the ACL graft were moderate, with combined κ values of .41 and .49, respectively. The femoral tunnel position was vertical in 88% and anterior in 46%. On MRI, the ACL graft was read as intact in 24%; however, no graft was intact on arthroscopic evaluation or physical examination. The greatest discordance was between the physical examination and MRI, with a rate of 52%. An insidious-onset mechanism of injury was significantly associated with discordance between MRI and arthroscopic evaluation of the ACL ( P = .0003) and specifically with an intact ACL graft on MRI ( P = .0014). The sensitivity and specificity of MRI to detect an ACL graft tear were 60% and 87%, respectively. Conclusion: Caution should be used when evaluating a failed ACL graft with MRI, especially in the absence of an acute mechanism of injury, as it may be unreliable and inconsistent.